Changes in retinal nerve fiber layer and vessel densities after scleral buckling in patients with rhegmatogenous retinal detachment observed by OCTA - Zhang, Cuiwen; Liu, Linlin; Jiang, Yiping (Frontiers in Medicine, 2024)
PurposeTo observe the changes in peripapillary retinal nerve fiber layer (RNFL) thickness and peripapillary vessel densities (VD) in patients with rhegmatogenous retinal detachment (RRD) after scleral buckling (SB) by OCTA.MethodsA total of 40 patients (40 eyes) with monocular RRD who underwent SB were included in the study, with the operated eyes (40 eyes) as the study group and the contralateral healthy eyes (40 eyes) as the control to analyse the changes in peripapillary RNFL thickness and VD before and after surgery. Data were analysed by paired samples t-test or Wilcoxon signed rank sum test.ResultsComparison of the peripapillary RNFL thickness in the 8 areas between the two groups during the 6-month follow-up period: All 8 peripapillary areas of the optic disc were statistically different before surgery, except for the tempo superior and tempo inferior, which were statistically different at each postoperative follow-up point, and the remaining 6 areas in the operated eyes group were progressively closer to those in the healthy eyes group, and there was no significant difference between the two groups. Comparison of peripapillary VD in the 8 areas between the two groups during the 6-month follow-up: Peripapillary VD in the 8 areas in the two groups were all statistically different before surgery, and except for superior tempo, which was statistically different at each postoperative follow-up time point, the remaining seven areas in the operated eyes group became progressively closer to that in the healthy eyes group and there was no significant difference.ConclusionRRD negatively affects the peripapillary RNFL, but both peripapillary RNFL thickness and VD gradually improved in the operated eyes close to the contralateral eyes after SB.